Study on the decline of wildlife population in nature due to illegal breeding and hunting: Implications for biodiversity conservation - Rianzar, Muhammad; Kusuma, Hanif (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Poaching of wildlife, including protected species, is on the rise, partly due to increased demand in the world market. Therefore, this journal aims to examine the problems faced by Indonesia in dealing with wildlife trade crimes that still occur frequently, as well as the implementation of Law Number 5 of 1990 related to law enforcement for wildlife protection in Indonesia. Methods: The research method used is qualitative, by collecting data from books, articles, news, and journals. The analysis involved theories, concepts, legal principles, and regulations in the Act, as well as related case studies in Indonesia. Findings: The results show that although Indonesia has Law No. 5 of 1990, it is still lacking in effectiveness in reducing poaching and trade of wild and protected animals. Law enforcement officials and related agencies face various problems in the implementation of law enforcement. Community involvement in the endangered species trade is a key driver of the illegal keeping trend in Indonesia. Conclusion: The rate of prosecutions and convictions of illegal keepers remains low, creating inequalities in sentencing and giving the impression that the risks of this illegality are relatively low compared to the financial gains possible. Novelty/Originality of this article: This article highlights that collaboration between the government, communities and non-governmental organizations can provide additional support in conservation efforts and handling illegal cases.